The Physical Indicators of Quality of Life for Hemodyalisis Patients (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
The measurement of quality of life using physical indicators is required to validate the use of quality of life questionnaire. Physical indicators of quality of life for hemodialysis patients include interdialytic weight gain, edema, muscle strength, upper arm circumference and blood pressure. This study used an experimental research design with pre-test post-test approach. Samples were divided into an intervention group consist of 6 people and a control group consisting of 5 people which were randomly assigned. The study concludes that all physical indicators of quality of life have improved although not all indicators reach significant values. Physical indicators which experience significant improvement are muscle strength, upper arm circumference and systolic blood pressure after hemodialysis. There are significant differences of physical indicators of quality of life of the circumference of the upper arm, ankle circumference, edema and systolic blood pressure after hemodialysis between the experimental group and the control group.